2020
DOI: 10.3390/antibiotics9090616
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Antibiotic Resistance of Maltose-Negative Staphylococcus aureus in South African Dairy Herds

Abstract: Antibiotic resistance has been reported since the 1940s in both human and veterinary medicine. Many years of monitoring milk samples in South Africa led to identification of a novel maltose-negative Staphylococcus aureus (S. aureus) strain, which appears to be an emerging pathogen. In this study, the susceptibility of this strain to antibiotics was evaluated over time, during diverse seasons in various provinces and according to somatic cell count (SCC) categories. A data set of 271 maltose-negative S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
4
3
0
Order By: Relevance
“…The resistance of the maltosepositive S. aureus observed in a South African study (Karzis et al 2020a) was in agreement with that reported in other studies in Denmark and New Zealand (Salmon et al 1998).…”
Section: Staphylococcus Aureus Resistance In South Africa Compared To That Of Other Countriessupporting
confidence: 91%
See 4 more Smart Citations
“…The resistance of the maltosepositive S. aureus observed in a South African study (Karzis et al 2020a) was in agreement with that reported in other studies in Denmark and New Zealand (Salmon et al 1998).…”
Section: Staphylococcus Aureus Resistance In South Africa Compared To That Of Other Countriessupporting
confidence: 91%
“…Staphylococcus aureus resistance in South Africa compared to that of other countries: The resistance of the maltose-positive S. aureus observed in a South African study (Karzis et al 2020a ) was in agreement with that reported in other studies in Denmark and New Zealand (Salmon et al 1998 ). The relatively high resistance rates of S. aureus to penicillin and tetracycline in both the South African studies (Karzis et al 2020a ; Schmidt et al 2015 ) also corresponded with the findings of a recent study in Ethiopia (Kalayu et al 2020 ). Similarly, as in South Africa, most isolates from the United States (New York State), Argentina and Germany showed resistance to spiramycin (Monistero et al 2020 ).…”
Section: Review Findingssupporting
confidence: 88%
See 3 more Smart Citations